Does Sharia By-Laws Damage Interfaith Harmony? The Case of Sharia By-Laws Implementation in Pamekasan, Madura - Maimun, Maimun; Syawqi, Abdul Haq (IAIN Samarinda, 2020)
Since the beginning of the Reformation Era in 1998, Indonesia has been transforming itself into a more liberal polity than that of in the New Order Era. This political circumstance is characterized by the freedom of opinion and the decentralization of power. During this Reformation Era, many local regulations have been enacted. One of which was sharia by-laws or local regulation based on Islamic norms in some largely Muslim populated regions. This situation has triggered concerns about the impacts of sharia by-laws over the inter-religious harmony among a very diverse society of Indonesia. This study aims to evaluate the sharia by-laws implementation in Pamekasan, Madura, and analyze its implication for inter-religious harmony. By using a qualitative approach and phenomenological descriptive analysis, it reveals that there has not been found negative impacts on the implementation of sharia by-laws since its enactment in 2001 until today. The internal and external potentials of Pamekasan residents, arguably, have become the determinant factor in keeping the by-laws in line with inter-religious harmony. These potentials include cultural-deeply rooted social capitals such as friendliness, politeness, mutual respect, and helping others. Besides, dialogue among religious elites, which is facilitated either by local government or civilian organizations, is frequently conducted and this helps to create a conducive atmosphere for all despite the existence of sharia by-laws in Pamekasan, Madura.Keywords:Â sharia by-laws, interfaith harmony, social capitals.